Bosu Fitness : complete cardio, strength and core conditioning - Salminen, Marina Ꜳgꜳrd Elstrup, ....- (Lulu : Aagaard, 2013)
A comprehensive compilation of Bosu exercises and programs. Over 100 exercises plus variations and program design tips. Motivating one-on-one and group exercises for beginners, intermediate and advanced exercisers. More than 200 photos and step-by-step text on proper exercise technique. Expert tools and 'templates' for programming, e.g. agility, circuit and interval training workouts. The book features two unique programs: A complete Bosu total body cardio, strength and core conditioning workout - and a Bosu bodytoning workout. 'Bosu Fitness', is a valuable tool and reference book for physical exercise leaders, personal trainers, group exercise instructors, physiotherapists and Pe teachers using the Bosu and similar fitness equipment.
Keywords: Fitness